Recent Advances and Challenges of Small-Capacity Air-Cooled Solar-Assisted Ammonia Absorption Chillers in Tropical Regions - Desy Agung; Siti Astari Pratiwi; Adinda Rahmah Shalihah (Journal of Innovative and Creativity, 2026)
The rapidly increasing demand for air conditioning has intensified energy consumption, environmental impacts, and water use associated with conventional vapor compression cooling systems. Solar-powered absorption chillers offer a low-carbon alternative by utilizing renewable thermal energy and environmentally friendly working fluids. This paper presents a literature review on the development of solar-powered absorption chiller systems, with a focus on small-capacity, air-cooled chillers using ammonia as the working fluid. The review is structured chronologically, covering early feasibility studies through performance improvement, compact system design, and adaptation to hot and tropical climates. Compared to water-cooled systems, air-cooled configurations eliminate the use of cooling towers, thereby reducing water consumption and enabling simpler system designs, although they face challenges in heat rejection under high ambient temperatures. Ammonia–water systems show strong potential due to their high temperature tolerance, zero Global Warming Potential, and suitability for air-cooled operation. This review identifies key technological advances, major limitations, and important research gaps, particularly for applications in tropical regions such as Indonesia.